Respostas

A melhor resposta!
2014-03-19T18:28:06-03:00
A = [[ 1 3 ]], B =[[ 2 -1]] e C= [[ 0 -6 ]]
      [[ 2 4 ]]        [[ 4 0 ]]         [[ 4 2 ]]

a ) A + B 

[[1  3]]  + [[ 2  -1]]  =  [[ 3  2]]
[[ 2 4]]     [[ 4   0]]      [[ 6  4]]

b ) 2A - (B+C)

primeiro calculamos B + C 

[[ 2 -1]] + [[ 0 -6 ]] =  [[ 2 -7]]
[[ 4 0 ]]    [[ 4 2 ]]      [[ 8  2]]

agora calculamos 2A

2. [[ 1  3 ]] = [[ 2  6 ]]
    [[ 2  4 ]]    [[ 4  8 ]]

agora fazemos a subtração : 

[[ 2  6 ]] - [[2  -7]] = [[ 0 13 ]]
[[ 4  8 ]]   [[8   2]]    [[-4   6 ]]   → resultado final
1 5 1